A estrutura do grupo nominal no rema: a realização do dinamismo comunicativo - Saparas, Marcelo (2007)
This research examines the structure of the nominal group (NG) found within the Rheme in distinguished discourse genres, namely academic writing, movie review and opinion article. The NG has not been the object of many studies, and besides, it has been studied within isolated sentences and, in general, in sentences inauthentically constructed. However, there is no consensus, among researchers, neither on the function, nor on the order of its constituents. There are many factors that influence the constitution of the structure of the NG, among which the influence on the type of genre, according to Bathia´s and Whitaker´s researches in 1991 and 1995, respectively. I attempt, in this research, to: (a) examine authentic texts and not just isolated sentences, as it has been done, since the literature shows us that the structure of the NG involves textual concepts as those of Theme and Rheme, which, by extension, as we will see, are overlaid with informational issues of Given and New. I attempt, therefore, to relate the NG with the communicative dynamism to examine to what extent the constitution of the structure of the NG reflect off this dynamism. This way will lead us to consider the question of ensuring effective communication flow , through the notion of communicative dynamism, that increases, in most cases, from the Theme to the Rheme, according to Firbas (1974). Nevertheless, despite the fact that this research examines the Rheme, one has to take the Theme into account, seeing that; according to Halliday, quoted by Fries (2002), Rheme is all in the clause but the Theme . Here we run into a problem: it is known that the definition of Theme has aroused polemics. I must clarify that this research is conducted on the study of the NG within the Rheme, since this position is generally taken by the information newness, fact which marks it by a higher degree of communicative dynamism, and also because, although it occupies a crucial role in the discourse, little has been researched about it. This being the case, the objective of this research is to examine, in authentic texts, in three different discourse genres, the constitution of the NG in the Rheme, to find out how this structure is characterized in order to fulfill its function within the Rheme, in other words, the function of increasing the communicative dynamism. Thus, it is basically supported by the Systemic Functional Linguistics and by the Functional Sentence Perspective. Numerical data, in terms of clauses and adjuncts, will show the lexico-grammatical elements that constitute the NGs of the Rheme. Therefore, the data seem to indicate that the communicative dynamism makes use of attributes and the simple constitution of the greater part of the NGs in this process. A noteworthy fact is the widespread occurrence of definite articles in places that serve to convey new information, the Rheme. There are rare occurrences of noun clauses and adjectives in pre-head positions within the NG. The role of the circumstances is also important in this context, for it seems to contribute to explain the way the event occur, in space and time determined by it. There are occurrences of comparisons with the preposition como ( like ), to explain through comparisons the content that is hardest to learn